2006
DOI: 10.1074/jbc.m513499200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Molecular Basis of the Drosophila Mutations in Carboxypeptidase D

Abstract: Carboxypeptidase D (CPD) functions in the processing of proteins and peptides in the secretory pathway. Drosophila CPD is encoded by the silver gene (svr), which is differentially spliced to produce long transmembrane protein forms with three metallocarboxypeptidase (CP)-like domains and short soluble forms with a single CP domain. Many svr mutants have been reported, but the precise molecular defects have not been previously determined. In the present study, three mutant lines were characterized. svr Metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(86 citation statements)
references
References 51 publications
4
80
1
1
Order By: Relevance
“…taining multiple carboxypeptidase domains and it has been proposed that this special structure increases the range of pH at which it can be active, ensuring activity throughout the secretory pathway (Novikova et al 1999). The Drosophila silver protein contains three carboxypeptidase domains, a transmembrane domain, and a cytosolic tail (Sidyelyeva and Fricker 2002). We found that three independent loss-of-function mutations in the silver gene act as enhancers of Ab-induced phenotypes.…”
Section: Resultsmentioning
confidence: 79%
“…taining multiple carboxypeptidase domains and it has been proposed that this special structure increases the range of pH at which it can be active, ensuring activity throughout the secretory pathway (Novikova et al 1999). The Drosophila silver protein contains three carboxypeptidase domains, a transmembrane domain, and a cytosolic tail (Sidyelyeva and Fricker 2002). We found that three independent loss-of-function mutations in the silver gene act as enhancers of Ab-induced phenotypes.…”
Section: Resultsmentioning
confidence: 79%
“…Unlike all other MCPs, CPD contains multiple CP-like domains. Human, rat, mouse, bovine, duck, chicken, and Drosophila CPD all contain three CP-like domains [37][38][39][40]. It is remarkable that only the first two CPlike domains contain all of the requisite active site and substrate-binding residues; the third domain is more similar to the CPX1/2 family members in that it lacks residues considered critical for enzymatic activity and is devoid of activity toward standard CP substrates [41].…”
Section: Occurrence and Biological Function Of N/e Mcpsmentioning
confidence: 96%
“…Of the conserved residues, His69, Glu72, and His196 (Gln in the MDCP-A1 group) are involved in zinc binding, whereas Arg71, Arg127, and Arg145 along with Tyr248 (His in the MDCP-A1 group) and Glu270 (either Leu or Ile in the MDCP-A1 group) are involved in substrate binding and cleavage (Auld, 1998;Estebanez-Perpina et al, 2001). carboxpeptidase-like domain with similar size (Sidyelyeva and Fricker, 2002). The sequence identity between MDCP-D and the Drosophila carboxypeptidase D is 56%.…”
Section: Isolation Of Carboxypeptidase Cdnasmentioning
confidence: 98%